Kinetic stability of nitrogen cubane inside the fullerene cage: Molecular dynamics study. Issue 4 (2nd April 2020) - Gimaldinova, Margarita A.; Katin, Konstantin P.; Grishakov, Konstantin S.; Maslov, Mikhail M.
Abstract: Using tight-binding molecular dynamics simulations, we study kinetic stability of the nitrogen cubane inside the fullerene carbon cage. The main identified mechanism of N8 decomposition is the N–N bond breaking with the further rapid "splitting" into the N2 molecules that can form the strong covalent bonds with the inner surface of the fullerene cage. It is found that the fullerene cage significantly increases the stability of the N8 cube, but its lifetime at room temperature is insufficient to observe the endohedral complex N8 @C60 without the use of extreme temperature conditions. It can be synthesized and investigated only at cryogenic temperatures.